Front Cover. Issue 11 (23rd October 2017) - Nowak, Sabina; Mysłajek, Robert W.; Szewczyk, Maciej; Tomczak, Patrycja; Borowik, Tomasz; Jędrzejewska, Bogumiła
Abstract : The cover image, by Sabina Nowak et al., is based on the Biodiversity Research Sedentary but not dispersing wolves Canis lupus recolonizing western Poland (2001–2016) conform to the predictions of a habitat suitability model, DOI: 10.1111/ddi.12621 . Photo Credit: Robert Myslajek.